2015
DOI: 10.1007/s10637-015-0228-4
|View full text |Cite
|
Sign up to set email alerts
|

Convection-enhancement delivery of platinum-based drugs and LipoplatinTM to optimize the concomitant effect with radiotherapy in F98 glioma rat model

Abstract: The prognosis for patients with glioblastoma remains poor with current treatments. Although platinum based drugs are sometimes offered at relapse, their efficacy in this setting is still disputed. In this study, we use convection-enhanced delivery (CED) to deliver the platinum-based drugs (cisplatin, carboplatin, and Lipoplatin ™ -liposomal formulation of cisplatin) directly into the tumor of F98 glioma-bearing rats that were subsequently treated with γ radiation (15 Gy). CED increased by factors varying betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
25
1
Order By: Relevance
“…27 F98 cells (10,000 cells in 5 µL) were prepared and implanted into the right caudate nucleus (1 mm anterior, 3 mm right of the bregma, and 6 mm deep) of the brain in 5 min. The convection-enhanced delivery (CED) procedure 28 was performed 10 days after implantation of F98 cells, at the same injection site using a 33 gauge Hamilton syringe. Before infusion, the burr was filled with bone wax and the needle was inserted 6.5 mm deep, retained there for 5 min and then withdrawn to 6 mm.…”
Section: Convection-enhanced Delivery In F98 Glioma Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…27 F98 cells (10,000 cells in 5 µL) were prepared and implanted into the right caudate nucleus (1 mm anterior, 3 mm right of the bregma, and 6 mm deep) of the brain in 5 min. The convection-enhanced delivery (CED) procedure 28 was performed 10 days after implantation of F98 cells, at the same injection site using a 33 gauge Hamilton syringe. Before infusion, the burr was filled with bone wax and the needle was inserted 6.5 mm deep, retained there for 5 min and then withdrawn to 6 mm.…”
Section: Convection-enhanced Delivery In F98 Glioma Modelmentioning
confidence: 99%
“…For this reason, we choose to assess Cu(DDC) 2 (prepared in DSPC/Chol liposomes) in an orthotopic F98 (rat glioblastoma) model, where treatment was administered directly into the site of tumor inoculation by CED. 28 The glioblastoma line was of interest because previous publications suggested that DSF and its metabolite DDC in the presence ) were inoculated subcutaneously into rag-2M mice and the tumors were treated intravenously with vehicle (sh buffer, ), coppercontaining liposomes (1.3 mg/kg, ) or cu(DDc) 2 (8 mg/kg, ) formulated in DsPc/chol liposomes using a M, W, F ×2 dosing schedule. Tumor volumes were measured 3 times a week and are plotted as mean ± standard error of the man (up to 9 mice per group).…”
Section: Cu(ddc) 2 Efficacy In Models Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Ten days after the implantation of F98 cells, CED procedure was performed with a 33 Ga Hamilton syringe (Hamilton Company, Reno, NV). Oxaliplatin and Lipoxal™ infusions were initiated at the same position as the F98 cell implantation, and done at a rate of 0.5 μl/min for 20 min [25]. Before and after infusion, the needle was maintained in a stationary position for 5 min and finally slowly withdrawn during 6 min.…”
Section: Ced Proceduresmentioning
confidence: 99%
“…For example, platinum drugs were previously abandoned for treatment of glioma due to their poor passage across the blood-CNS barrier, but are now being re-explored for localized delivery. Adding to the fact that they are not a substrate for principle efflux transporters in the brain, the inability of these agents to cross the blood-CNS barrier may now prove to be an advantage in prolonging the half-life and therapeutic effect of the drug [11][12][13] . Gliadel wafers, a carmustine-imbedded polyanhydride copolymer matrix implant, have perhaps been the most successful localized therapy and are FDA approved for newly diagnosed and recurrent glioblastoma, modestly extending overall survival of both groups 14 .…”
mentioning
confidence: 99%